The Role of Time Management in Enhancing Classroom Management Analytical Study of the Opinions of a Number of Principals and their Assistants in Basic Schools on the Outskirts of the Erbil Governorate - Nawzad Faithe Jamil Nadr; Abdulkhalq Nadr Qader (Zanco Journal of Humanity Sciences)
This research seeks to uncover the role of time management in enhancing classroom management in basic schools in the outskirts of the erbil governorate, to identify the extent to which principals and their assistants in basic schools have a clear vision of the two variables and their importance in achieving effectiveness. This research presented a theoretical framework on time management as an independent variable. It depends on five dimensions, namely: (Time Planning, Time Organizing, Setting  Goals  and Prioritizing Time, Time Direction, Follow- Up and censorship  Time ), and strengthening classroom management as an approved variable, and the field side was also adopted to identify the nature of the relationship and the impact between the two variables, and to reach According to the objectives of this research, the research adopted the descriptive and analytical approach in dealing with its variables. A hypothetical outline of the research was designed expressing its main hypotheses. The questionnaire was used as a tool to collect data and it was distributed to (206) principals and assistants in (100) basic schools as a sample of the research of 700 principals and their assistants. Administrative experiences in (250) basic schools as a community for research, and (200) questionnaires were retrieved valid for analysis, and a set of statistical methods were used to determine the results and through The software computer spss.v.24. The research reached the group of conclusions, the most important of which is the existence of a moral relationship between the dimensions of the independent variable collectively and individually and the adopted variable, classroom management, that time management in schools is the most important dimension of classroom management, as well as the presence of a moral impact relationship for the dimensions of time management in strengthening classroom management. After "setting goals and priorities," time is the most influential dimension in enhancing classroom management in basic schools. The research ended with a set of proposals in line with the conclusions to strengthen the base of this sector in addition to education.